Genome insights into the plant growth-promoting bacterium Saccharibacillus brassicae ATSA2T - Lingmin Jiang; Jiyoon Seo; Yuxin Peng; Doeun Jeon; Soon Ju Park; Cha Young Kim; Pyoung Il Kim; Chul Hong Kim; Ju Huck Lee; Jiyoung Lee (AMB Express, 2023)
Abstract Endophytes can facilitate the improvement of plant growth and health in agriculturally important crops, yet their genomes and secondary metabolites remain largely unexplored. We previously isolated Saccharibacillus brassicae strain ATSA2T from surface-sterilized seeds of kimchi cabbage and represented a novel species of the genus Saccharibacillus. In this study, we evaluated the plant growth-promoting (PGP) effect of strain ATSA2T in kimchi cabbage, bok choy, and pepper plants grown in soils. We found a significant effect on the shoot and root biomass, and chlorophyll contents following strain ATSA2T treatment. Strain ATSA2T displayed PGP traits such as indole acetic acid (IAA, 62.9 μg/mL) and siderophore production, and phosphate solubilization activity. Furthermore, genome analysis of this strain suggested the presence of gene clusters involved in iron acquisition (fhuABD, afuABC, fbpABC, and fepCDG) and phosphate solubilization (pstABCHS, phoABHLU, and phnCDEP) and other phytohormone biosynthesis genes, including indole-3-acetic acid (trpABCDEFG), in the genome. Interestingly, the secondary metabolites cerecidin, carotenoid, siderophore (staphylobactin), and bacillaene underlying plant growth promotion were found in the whole genome via antiSMASH analysis. Overall, physiological testing and genome analysis data provide comprehensive insights into plant growth-promoting mechanisms, suggesting the relevance of strain ATSA2T in agricultural biotechnology.